Faktor-Faktor Yang Berhubungan Dengan Pemilihan Alat Kontrasepsi Jangka Panjang (Paritas, Jarak Kehamilan, Dan Status Gizi) - Khoirun Nizaq; Anik Sri Purwanti (Journal of Innovative and Creativity, 2025)
Introduction: To improve the health status of mothers and children, a family planning program is implemented. The family planning program has various method options, one of which is the Long-Term Contraceptive Method, which is an effective contraceptive option to reduce the birth rate and delay fertility in women of childbearing age. The purpose of this study was to determine whether or not there was a relationship between parity, pregnancy spacing, and nutritional status with the selection of long-term contraception. Methods: This study used a cross sectional research design. Data collection was carried out using the observation method with a total sample of 30 respondents. Data analysis technique using Chi Square test. Results: The results of the study using the chi square test showed that the p value of parity was 0.00, the p value of pregnancy distance was 1.4, and the p value of nutritional status was 0.01. Conclusion: Parity and nutritional status have a significant relationship with the selection of long-term contraceptives.